PENGARUH KEPUASAN KERJA, MOTIVASI KERJA, KOMITMEN ORGANISASI TERHADAP TURNOVER INTENTION PADA KARYAWAN CV SURYA AGUNG MOTOR BANYUMAS - Galih Novagiti Ekarahman; Hermin Endratno (Media Ekonomi, 2017)
This study aimed to determine the effects of the variables of job satisfaction, work motivation and organizational commitment on turnover intention. In this study, the researcher conducted the sampling by distributing questionnaires to the respondents by survey method. The sampling technique was saturated sampling. The total sample was 35 respondents. This analysis used SPSS 16 for windows. The data was analyzed by validity, reliability test, classic assumtion test and multiple linear regression analysis.The research by partial test (t test) showed that job satisfaction, work motivation positive affected on turnover intention. Then the organization commitment had a significant negative effect on turnover intention. The results by simultaneous test (F test) indicated that job satisfaction, working motivation and organizational commitment had positive effects on turnover intention.